Impact of Japan International Co-Operation Agency (JICA) Extension Project on Quality Silk Production: a Case Study - P. Kumaresan; R.G. Geetha Devi; C.K. Kamble (Journal of Agricultural Extension Management, 2025)
Sericulture, as an agro-based enterprise, occupies an important position in Indian economy due to its high employment potential, low capital intensive and remunerative nature of the production that churns out value added products of economic importance. India is the second largest producer of raw silk, next only to China accounting for more than 13 per cent of the global silk production. The total annual production of raw silk in India was 18.48 thousand MT, of which mulberry raw silk output aggregated to about 16.53 thousand MT during 2006-07. However, the major concern of the Indian silk industry is the low level of quality and productivity as compared to other major silk producing countries such as China and Brazil. The major reason for the above problem is that the silk is produced by the use of crossbreed cocoons for reeling raw silk. The silk reeled out of these crossbreed cocoons produced in India reaches a maximum grade of C by the international standards. This silk is not preferred in the high-speed looms and mill sectors due to less uniformity, short filament length, more winding breaks and high degumming losses as compared to imported silk (Naik and Babu, 1992